Pemberdayaan Anak Sekitaran Sungai Deli Melalui Pelatihan Pembuatan Sabun Cair Berbasis Bunga Telang - Joya Kharismaylinda; Lia Satriani Ramdhan Farsiah; Ega Putri Andira Nasution; Finny Cornelia Sitinjak; Faradiza Salsabila; Muhammad Taufiq; Khairunnisa Sipahutar; Nurjannah, Nurjannah (CV. ITTC INDONESIA, 2025)
Improving community skills, especially among children, in utilizing natural ingredients into economically valuable products formed the basis of the liquid soap-making training based on butterfly pea flowers held at Sanggar Sungai Deli Medan. This activity aimed to enhance knowledge of the potential of butterfly pea flowers as environmentally friendly organic materials and to foster entrepreneurial spirit rooted in local wisdom. The implementation method included education, live demonstrations, and hands-on practice with participants. The results of the training showed increased participant skills in independently producing liquid soap and growing interest in developing it into a business opportunity. These results are important as an initial step in community empowerment through education and innovation of sustainable natural products.